Effect of Tax Revenues on Economic Growth in Benin: The Role of Investment - NONVIDE, Gbêtondji Melaine Armel; AMEGNAGLO, Cocou Jaures (Journal of Advanced Studies in Finance; Vol 8 No 2 (2017): JASF Volume VIII Issue 2(16) Winter 2017DO - 10.14505//jasf.v8.2(16).03, 2018)
Benin's economy relies mainly on tax revenues. This paper analyses the role of investment in the relation between tax revenue and economic growth in Benin. It employed the Fully Modified Ordinary Least Squares technique to estimate the long run relationship among the variables of the model. Results indicate positive effect of tax revenues on economic growth. This effect is improved by the private investment while deteriorated by public investments which level remains low. This result emphasizes the problem of public resources allocation in Benin. Other determinants of economic growth include investment, annual population growth rate, and trade. The study recommends that fiscal policy must promote private investments. Tax revenues must be directed to more productive investments. The results also favour trade open policy.